2018
DOI: 10.1063/1.5049750
|View full text |Cite
|
Sign up to set email alerts
|

Mean field phase synchronization between chimera states

Abstract: We study two-layer networks of identical phase oscillators. Each individual layer is a ring network for which a non-local intra-layer coupling leads to the formation of a chimera state. The number of oscillators and their natural frequencies is in general different across the layers. We couple the phases of individual oscillators in one layer to the phase of the mean field of the other layer. This coupling from the mean field to individual oscillators is done in both directions. For a sufficient strength of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Recently, a prominent line of research emerged which studies chimera states in multilayer networks [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57]. Multilayer networks are important modelling tools for complex systems such as transportation networks, social interactions and the brain [58,59].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, a prominent line of research emerged which studies chimera states in multilayer networks [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57]. Multilayer networks are important modelling tools for complex systems such as transportation networks, social interactions and the brain [58,59].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, Ref. [50] was the first study on chimera states in a network with layers of different sizes. There the authors modelled a mean field interlayer coupling and observed that the phases of the order parameters of the two layers synchronize [50].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[61][62][63][64][65][66][67][68] Nowadays, the attention of researchers is focused on the effects that can occur not only in isolated (individual) ensembles but in large systems of interacting ensembles. The interaction between ensembles (layers) in multilayer networks can lead to different types of synchronization of complex spatiotemporal structures, including chimeras, e.g., cluster synchronization, 73,74 complete synchronization, 75 generalized synchronization, 76 phase synchronization, 77 external and mutual synchronization, [78][79][80] explosive synchronization, [81][82][83] etc.…”
Section: Introductionmentioning
confidence: 99%
“…Current research in the field of complex systems is moving beyond simple network structures to more complicated, realistic topologies. One of them are multilayer networks, which find a wide range of applications in nature and technology, such as neuronal and genetic networks, social networks, power grids, transportation networks [78][79][80][81][82][83][84][85][86][87][88][89][90][91]. Recent studies have been focused on various synchronization scenarios in multilayer structures, including remote and relay synchronization [92][93][94].…”
Section: Introductionmentioning
confidence: 99%